ACTIVATION OF HEPARIN COFACTOR II BY PHOSVITIN, A PHOSPHOGLYCO-PROTEIN, AND OTHER PHOSPHATE-CONTAINING POLYANIONS - Church, F C; Treanor, R E; Whinna, H C (Thrombosis and Haemostasis, 1987)
We are characterizing the specificity of the polyanion-binding domain of the heparin/dermatan sulfate-dependent plasma protease inhibitor, heparin cofactor II (HCII). Various phosphate-containing polyanions accelerate the HCII-catalyzed inhibition of thrombin (T). Phosvitin, a phosphoprotein, enhances the HCII/T reaction at 25°C and pH 8.0 with the apparent second-order rate constant value (K2) increasing from 5 × 104 M−1 min−1 (in the absence of phosvitin) to 8 x 10' M”1 min as phosvitin increased from 0.05 to 30 ug/ml and then decreases as phosvitin is increased above 30 ug/ml. Apparent dissociation constant values for phosvitin-HCII and phosvitin-T are 450 nM and 10 nM, respectively. Polynucleotides accelerate the HCII/T reaction and have the following specificity (concentrations examined from 1-200 ug/ml): poly(guanylic acid) >> poly(adeny-lic acid, guanylic acid) > poly(inosinic acid) > poly(guanylic acid, uridylic acid) > poly(uridylic acid) = poly(adenylic acid) > poly(cytidylic acid). Polyphosphate anions (phosphate chain length, n, ranging from 5-100) enhance the HCII/T reaction. When compared at an equimolar phosphate concentration (1 mM), the rate was saturated at n = 50 with a maximum V.2 of about 5 × 107 M−1 min−1. Ca2+ (or Mg2+)-phosvitin/polyphosphate anion complexes and salmon protamine-polynucleotide complexes have lost the ability to enhance the HCII/T reaction. Phospho-pyridoxylated-HCII (lysine modified), with greatly reduced heparin cofactor activity, has lost its accelerating effect with phosvitin, polynucleotides and the polyphosphate anions. None of the above mentioned polyphosphate-containing compounds are effective at accelerating either the HCII-catalyzed inhibition of chymotrypsin or the antithrombin Ill-catalyzed T reaction. Our results suggest that (i) HCII is activated by the multiple negative charges of phosphate polyanions but they alone are not sufficient; (ii) the effective phosphate polyanions must also possess a specific conformation for maximum activity; and (iii) the phosphoserine-containing protein, phosvitin, can serve as a "template" for HCII/T.